The effects of the strategy and goal on business performance as mediated by management accounting systems - Nimnual Visedsun; Kanitsorn Terdpaopong (Economies, 2021)
Previous research in the literature often investigated the associations between management accounting systems and the success of organizations. However, little has been done in regard to the association of business strategies, goals, and firms' performance while having management accounting tools as mediators. Management accounting systems are classified as traditional and strategic management accounting themes. Each theme, of course, implements different accounting tools. This article explores the degree to which, as mediated by management accounting systems, the business strategies and business goals of large Thai manufacturing companies influence their financial and non-financial performance. To gather the data, a survey questionnaire was developed. Of the 1500 companies selected for inclusion in the survey, 205 provided completed and usable responses for a response rate of 13.67%. Structural equation modeling (SEM) was used to analyze the relationships among the variables. The findings shed some light on what the management of a firm could expect concerning organizational performance from their business strategies, business goals, and the implementation of specific management accounting systems. Corporate strategies and corporate goals had a statistical influence on both the financial and non-financial performance of the large corporations in Thailand when mediated via strategic management accounting systems, while there was no influence when mediated by traditional management accounting systems. A greater understanding of the relationships and effects of which mediators should have been employed in organizations to bring forth business strategies and business goals and generate productive results for organizational performance is provided by this research. Choosing the appropriate performance mediators can help achieve corporate strategies and goals.
Keywords: 330; business goals; business strategies; financial performance; management accounting systems; manufacturing companies; non-financial performance